2022
DOI: 10.1038/s41467-022-34319-0
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the liquid gliding on vibrating solid liquid interfaces with dynamic nanoslip enactment

Abstract: Slip length describes the classical no-slip boundary condition violation of Newtonian fluid mechanics, where fluids glide on the solid surfaces. Here, we propose a new analytical model validated by experiments for characterization of the liquid slip using vibrating solid surfaces. Essentially, we use a microfluidic system integrated with quartz crystal microbalance (QCM) to investigate the relationship between the slip and the mechanical response of a vibrating solid for a moving fluid. We discover a liquid sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Particle coalescence/agglomeration resulting from liquid bridge adhesion plays a significant role in various vital areas such as the pharmaceutical and food industry, 1−3 soft matter and cell biology, 4,5 controlling the fluid flow, 6 and solid−liquid interfaces. 7 Capillary force is a meniscus force due to condensation typically observed in a wet medium. To model and simulate the capillary force, the nonlinearity of the capillary equation combined with the variety of substrate geometries leads to a large number of solutions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Particle coalescence/agglomeration resulting from liquid bridge adhesion plays a significant role in various vital areas such as the pharmaceutical and food industry, 1−3 soft matter and cell biology, 4,5 controlling the fluid flow, 6 and solid−liquid interfaces. 7 Capillary force is a meniscus force due to condensation typically observed in a wet medium. To model and simulate the capillary force, the nonlinearity of the capillary equation combined with the variety of substrate geometries leads to a large number of solutions.…”
Section: Introductionmentioning
confidence: 99%
“…The study of capillary force has a long-time history and is considered a multidisciplinary field of research. Particle coalescence/agglomeration resulting from liquid bridge adhesion plays a significant role in various vital areas such as the pharmaceutical and food industry, soft matter and cell biology, , controlling the fluid flow, and solid–liquid interfaces …”
Section: Introductionmentioning
confidence: 99%
“…A recent example of such a study is demonstrated by Payam et al 6 Here, the authors discover a "missing liquid slip" in the…”
Section: ■ "Active Solid"−"moving Liquid" Interface In Bio/chemical S...mentioning
confidence: 91%
“…A recent example of such a study is demonstrated by Payam et al Here, the authors discover a “missing liquid slip” in the vibrating solid–liquid systems such as the QCM-based biosensor (Figure a shows their system) where traditionally frequency and dissipation changes were interpreted exclusively with mass change on the sensor surface, irrespective of the flow conditions. To some extent the study also argued the origin of the liquid slip by correlating the slip to a large extent with the flow rate of the liquid, rather than the surface wetting conditions.…”
Section: “Active Solid”–“moving Liquid” Interface In Bio/chemical Sen...mentioning
confidence: 98%
See 1 more Smart Citation